2020
DOI: 10.1177/2055102920975975
|View full text |Cite
|
Sign up to set email alerts
|

Risk and protective factors for intention of contraception use among women in Ghana

Abstract: The use of various forms of contraception in Ghana gained prominence after the government resorted to investing more in family planning programs when maternal mortality was declared an emergency in the country. In Ghana, the intention to use and actual usage of contraceptives is influenced by many factors, which may lead to non-usage or discontinuation. This quantitative study was conducted to determine risk and protective factors impacting on the intention and usage of contraceptives. Survey data from the Gha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 23 publications
2
17
1
Order By: Relevance
“…The current educational motivation due to different international efforts like the sustainable development goals might influence these things. Participants in the study in Gahanna showed the reverse intention compared to our study; the participants with primary education as their highest education had no intent to use contraceptive methods in that study [ 2 ]. That might indicate an intention to learn and use contraception was correlated; however, the status of the relationship was not clear.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…The current educational motivation due to different international efforts like the sustainable development goals might influence these things. Participants in the study in Gahanna showed the reverse intention compared to our study; the participants with primary education as their highest education had no intent to use contraceptive methods in that study [ 2 ]. That might indicate an intention to learn and use contraception was correlated; however, the status of the relationship was not clear.…”
Section: Discussionmentioning
confidence: 70%
“…A woman may incline toward contraceptive method use even though many factors might make things difficult for her. The intention to use contraceptive methods is associated with some socio-demographic variables in Africa [ 2 ]. The socio-demographic factors of the women like age, place of residence, marital status, education, religion, work, frequency of visit to health institution, and awareness of the ovulation cycle have reported affecting intention to use contraception methods [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…A person’s intention to perform a behavior is driven by perceived costs and motivation [ 5 ]. Intention to use and use of family planning has been the best method to control family size and unnecessary pregnancies [ 6 ]. Even the intention to use contraceptives improves the health of children, women, families, and whole societies [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…In terms of the participants' education level, our study shows that young males pursuing a bachelor's or young females pursuing a master's degree tend to have higher FCU. Previous studies can partly explain this phenomenon: with a higher degree of education, students may have more opportunities to learn sexual knowledge and raise awareness of contraception [28,29].…”
Section: Discussionmentioning
confidence: 99%